2015
DOI: 10.1080/07448481.2015.1085057
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of well-being among college students

Abstract: Interventions that promote sleep quality among college students may be most beneficial in improving well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 48 publications
4
56
0
14
Order By: Relevance
“…Furthermore, sleep quality emerging as a significant outcome in our sample parallels a recent article by Ridner and colleagues that found that sleep quality was the strongest predictor of well-being among college students. 52 Ridner called for interventions to promote sleep quality as a means of improving well-being in this population. 52 Our results add to this body of literature by exploring the determinants that affect sleep quality and therefore influence well-being among college students.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sleep quality emerging as a significant outcome in our sample parallels a recent article by Ridner and colleagues that found that sleep quality was the strongest predictor of well-being among college students. 52 Ridner called for interventions to promote sleep quality as a means of improving well-being in this population. 52 Our results add to this body of literature by exploring the determinants that affect sleep quality and therefore influence well-being among college students.…”
Section: Commentmentioning
confidence: 99%
“…52 Ridner called for interventions to promote sleep quality as a means of improving well-being in this population. 52 Our results add to this body of literature by exploring the determinants that affect sleep quality and therefore influence well-being among college students.…”
Section: Commentmentioning
confidence: 99%
“…Este per l está em linha com estudos prévios nesta população quer nacionais quer internacionais Eurostudent, 2012(Hauschildt, Gwosć, Netz, & Mishra, 2015. Constatou-se que taxas de prevalência de consumos de álcool e drogas são ligeiramente inferiores aos valores reportados pela maioria dos estudos (Bayati, Beigi, & Salehi, 2009;Ridner et al, 2015). A prática moderada de exercício físico/desporto pelos participantes é um dado positivo inesperado, contrariando a generalidade os estudos que indicam que os EES deixam de ter disponibilidade para praticar exercício físico (Ferrara, 2009).…”
Section: Introductionunclassified
“…Também se constatou que aqueles que dormem mais horas de sono por dia em tempo aulas têm níveis de saúde mental mais elevados. Os nossos resultados estão em linha com outros estudos recentes nesta população (Ridner et al, 2015;Kenari, 2014 …”
Section: Introductionunclassified
“…The rst and therefore strongest predictor selected into the submodel was sleep quality -how refreshed a participant felt after waking up, on their average day. Sleep quality has been consistently shown to be one of the strongest predictors of well-being, especially in young adults, with poor sleep quality being strongly linked to poor mental health outcomes including symptoms of depression (Pilcher et al, 1997;Ridner et al, 2016;Wallace et al, 2017;Wilson et al, 2014). Further, it is important to note that while sleep quality is often shown to be an important predictor of well-being, sleep quantity is not (Pilcher et al, 1997;Wallace et al, 2017).…”
Section: Discussionmentioning
confidence: 99%